Adoption of Climate Resilient Agro-Ecological Practices in the Karnali River Basins - GC, Sagar; Rana, Ram Bahadur; Bishwokarma, Parshuram; BK, Buddha Bahadur (Journal of Agriculture and Resource Management, 2024)
Karnali province, with an HDI of 0.53, cannot compete with other provinces on production and productivity due to mountainous terrains. It is rich in agrobiodiverisy and indigenous knowledge systems shaped by diverse climate, culture and food systems which allow to practice agro-ecology based production systems. The promotion of local, safe and healthy food systems through the adoption of ecological practices is the only option to get better return from agricultural production and improve the food and nutrition insecurity of the province. The study aims to identify the climate resilient agro-ecological practices practiced by the people and how the socio-economic condition of the people affects the adoption of such technologies and practices. Data collected through household surveys, Focus Group Discussion (FGD) and Key Informant Interviews (KII) from the Karnali river basin districts were analyzed using descriptive and inferential statistics. Results showed that eighteen different climate resilient agro-ecological practices categorized under six different headings such as cropping/planting method, resilient seed/breed, disease and pest management, water management, carbon/nutrient management and farmer’s risk reduction were found being practiced by the farmers. The highest number of climate resilient ecological practices were found being practiced in pulses (11), followed by cereals, vegetables, and oil crops (10). Women were more trained in agro-ecological farming than men. Each variable of the socio-economic condition except caste and income showed a significant relationship with the adoption of climate resilient agro-ecological practices. Awareness along with participatory engagement of the various stakeholders in demonstrating the practices and generating evidence can be suggested to convince them to the promotion of agro-ecology.